The Elderly Expectations of the Caregiver’s Sociodemographic Preferences: a Qualitative Approach - Sharon Gondodiputro; Dahlia Santika Hutasoit; Lina Rahmiati (Global Medical & Health Communication (GMHC), 2019)
Prevalence of chronic diseases and disability will increase at the advancing age. In the future, the need for the caregiver will increase. Only few studies about the expectations of the elderly towards the sociodemographics status of the caregiver found. Unfulfilled expectations of the elderly towards their caregivers may cause both health and non-health issues. The purpose of this study was to explore the elderly expectations of the caregiver’s sociodemographic preferences. A qualitative study was carried out to 7 elderly aged 64–77 years old from July to August 2018 in Bandung city. These elderly selected from 7 integrated care posts (pos pembinaan terpadu/posbindu) that met the inclusion criteria: aged 60 years old and above; male or female; capable of communicating adeptly, and no dementia by undergoing the mini-mental state examination (MMSE). A one-on-one interview was conducted at the residence of the elderly using an interview guide consisted of several opened questions related to the caregiver’s sociodemographic preferences. A content analysis was carried out. This study discovered that the elderly preferred their family members or relatives whom they can trust to become their caregivers (their children and grandchildren). Most of these elderly also preferred daughters who live with them and has a decent income. If the family members could not become their caregiver then their neighbor or a community volunteer/cadre, they knew well, and trust to be their caregiver. It concluded that the elderly prefer their daughters who live with them and has a decent income to be their caregivers. EKSPEKTASI USIA LANJUT TERHADAP STATUS SOSIODEMOGRAFI CAREGIVER: SUATU PENDEKATAN KUALITATIFPrevalensi penyakit kronis dan disablilitas akan meningkat dengan pertambahan usia. Hal ini berdampak pada kebutuhan terhadap caregiver akan meningkat pula. Penelitian tentang ekspektasi usia lanjut terhadap status sosiodemografi caregiver belum banyak dilakukan. Ekspektasi usia lanjut merupakan faktor penting karena bila ekspektasi tersebut tidak terpenuhi maka akan berisiko timbul masalah kesehatan dan nonkesehatan. Tujuan penelitian ini mengeksplorasi ekspektasi usia lanjut terhadap status sosiodemografi caregiver. Studi kualitatif dilakukan terhadap 7 orang usia lanjut berusia 64–77 tahun pada Juli hingga Agustus 2018 di Kota Bandung. Para usia lanjut berasal dari 7 pos pembinaan terpadu (posbindu) yang memenuhi kriteria inklusi, yaitu usia ≥60 tahun, laki-laki atau perempuan, dapat berkomunikasi dengan baik, dan tidak demensia dengan dilakukan mini-mental state examination (MMSE). Wawancara dilakukan di kediaman informan masing-masing menggunakan panduan wawancara terkait pertanyaan dengan preferensi sosiodemografi caregiver. Analisis konten dilakukan. Studi ini menemukan bahwa usia lanjut lebih memilih anggota keluarga mereka yang dapat dipercaya untuk menjadi caregiver terutama anak dan cucu. Anak perempuan yang tinggal bersama usia lanjut dan memiliki penghasilan layak menjadi pilihan utama. Jika anggota keluarga tidak dapat menjadi caregiver maka tetangga atau kader yang mereka kenal baik dan dipercaya menjadi pilihan. Simpulan, pilihan utama caregiver bagi usia lanjut, yaitu anak perempuan mereka yang tinggal bersama dan memiliki penghasilan layak.